Peran Pemerintah dalam Mengatur Dampak Pertambangan Tanah di Kecamatan Tambang Ulang Berdasarkan UU Nomer 3 Tahun 2020 dan UU Nomer 38 Tahun 2004 - Hikmah Aulia (Sekolah Tinggi Ilmu Syariah Wal Aqidah Ash-Shofa Manonjaya, 2026)
This study aims to analyze the role of the government in regulating the impact of soil mining activities on public roads in Tambang Ulang District, South Kalimantan. Using a normative juridical approach, the research examines the effectiveness of the implementation of Law No. 3 of 2020 on Mineral and Coal Mining and Law No. 38 of 2004 on Roads. The findings indicate that although a regulatory framework exists, its implementation remains weak due to the centralization of licensing and oversight authority to the national government. This has limited the role of local governments in mitigating the negative impacts of mining. Poor inter-agency coordination, weak supervision, and a lack of firm law enforcement have allowed illegal mining activities to flourish. As a result, public roads suffer from severe damage, environmental pollution increases, and the health and comfort of local communities are compromised. Mining operators often neglect their obligations to carry out land reclamation and road maintenance, shifting the social and economic burden onto the surrounding population. This study recommends stronger synergy between central and local governments in monitoring and law enforcement, enhanced local capacity in environmental management, and increased community participation in overseeing mining activities. These efforts are essential to ensure that mining operations are conducted in a sustainable and responsible manner, without undermining public infrastructure and welfare.